At last!: An explicit solution for the Ramsey saddle path - Halvor Mehlum (University of Oslo, Department of Economics, 2002)
I derive an explicit solution for the saddle path in a Ramsey growth model. The existence of a closed form expression greatly simpliÞes the analysis of how the parameters of the utility function affects investments and growth.
Keywords: D91; O41; 330; Ramsey; growth; model; Optimales Wachstum; Theorie